The geometry of the tibial plateau and its influence on the biomechanics of the tibiofemoral joint - Hashemi, Javad; Chandrashekar, Naveen; Gill, Brian; Beynnon, Bruce D; Slauterbeck, James R; Schutt, Jr, Robert C; Mansouri, Hossein; Dabezies, Eugene (Journal of bone and joint surgery. American volume, 2008)
The geometry of the tibial plateau is complex and asymmetric. Previous research has characterized subject-to-subject differences in the tibial plateau geometry in the sagittal plane on the basis of a single parameter, the posterior slope. We hypothesized that (1) there are large subject-to-subject variations in terms of slopes, the depth of concavity of the medial plateau, and the extent of convexity of the lateral plateau; (2) medial tibial slope and lateral tibial slope are different within subjects; (3) there are sex-based differences in the slopes as well as concavities and convexities of the tibial plateau; and (4) age is not associated with any of the measured parameters. The medial, lateral, and coronal slopes and the depth of the osseous portion of the tibial plateau were measured with use of sagittal and coronal magnetic resonance images that were made for thirty-three female and twenty-two male subjects, and differences between the sexes with respect to these four parameters were assessed. Within-subject differences between the medial and lateral tibial slopes also were assessed. Correlation tests were performed to examine the existence of a linear relationship between various slopes as well as between slopes and subject age. The range of subject-to-subject variations in the tibial slopes was substantive for males and females. However, the mean medial and lateral tibial slopes in female subjects were greater than those in male subjects (p < 0.05). In contrast, the mean coronal tibial slope in female subjects was less than that in male subjects (p < 0.05). The correlation between medial and lateral tibial slopes was poor. The within-subject difference between medial and lateral tibial slopes was significant (p < 0.05). No difference in medial tibial plateau depth was found between the sexes. The subchondral bone on the lateral part of the tibia, within the articulation region, was mostly flat. Age was not associated with the observed results. The geometry of the osseous portion of the tibial plateau is more robustly explained by three slopes and the depth of the medial tibial condyle.